The potential contribution of terrestrial nature‐based solutions to a national 'net zero' climate target. Issue 11 (6th September 2021) - Bradfer‐Lawrence, Tom; Finch, Tom; Bradbury, Richard B.; Buchanan, Graeme M.; Midgley, Andrew; Field, Rob H.
Abstract: Many national governments have incorporated nature‐based solutions (NbS) in their plans to reduce net greenhouse gas emissions. However, uncertainties persist regarding both feasibility and consequences of major NbS deployment. Using the United Kingdom as a national‐level case study, we examined the potential contribution of three terrestrial NbS: peatland restoration, saltmarsh creation and woodland creation. While there is substantial political and societal interest in these three NbS, they also have strong potential for competition with other land uses, which will be a critical barrier to substantial deployment. We conducted a national mapping exercise to assess the potential area available for woodland creation. We then assessed the combined climate change mitigation potential to 2100 for the three NbS options under a range of ambition levels. In line with the most ambitious targets examined, 2 Mha of land is potentially available for new woodland. However, climate change mitigation benefits of woodland are strongly dependent on management choices. By 2100, scenarios with a greater proportion of broadleaved woodlands outsequester non‐native conifer plantations, which are limited by regular timber harvesting. Peatland restoration offers the greatest mitigation per unit area, whilst the contribution from saltmarsh creation is limited by the small areas involved. Overall, the contribution of these NbS to the United Kingdom's net zero emissions target is relatively modest. Even with the most ambitious targets considered here, by 2100, the total cumulative mitigation from the three NbS is equivalent to only 3 years' worth of UK emissions at current levels. Policy implications . Major deployment of nature‐based solutions (NbS) is possible in the United Kingdom but reaching 'net zero' primarily requires substantial and sustained reductions in fossil fuel use. However, facilitating these NbS at the national scale could offer many additional benefits for people and biodiversity. This demands that policy‐makers commit to a UK‐wide strategic approach that prioritises the 'nature' aspect of NbS. In the push to reach 'net zero', climate change mitigation should not be used to justify land management practices that threaten biodiversity ambitions. Abstract : Major deployment of nature‐based solutions (NbS) is possible in the United Kingdom but reaching 'net zero' primarily requires substantial and sustained reductions in fossil fuel use. However, facilitating these NbS at the national scale could offer many additional benefits for people and biodiversity. This demands that policy‐makers commit to a UK‐wide strategic approach that prioritises the 'nature' aspect of NbS. In the push to reach 'net zero', climate change mitigation should not be used to justify land management practices that threaten biodiversity ambitions.